Credit Risk Management System in China Construction Bank and Application of CreditMetrics - Zhang, Jiaying (2007)
The purpose of the dissertation is to assess the credit risk management system in China Construction Bank. Credit risk has long been a problem faced by banking industry. The emerging various financial instruments widen the sources of credit risk, which, at the same time, raise the probability and the exposure size of credit risk to banks. The recent turmoil of the US secondary mortgage market triggers a global credit squeeze. It causes not only bankruptcy of related banks, recession of the U.S housing market, but also the fluctuation of global exchange market. Bear with the severity of losses that credit risk can cause, efficient credit risk management system is vital for a bank's profitability, and competitiveness.